To solve this system of equations using the elimination method, we need to eliminate one of the variables by adding or subtracting the equations.
First, let's multiply the second equation by 3 to make the coefficients of x in both equations equal:
3x + 6y = 21
-15x + 6y = 39
Now, we can add the two equations to eliminate y:
(3x + 6y) + (-15x + 6y) = 21 + 39
-12x = 60
x = -5
Now that we have found the value of x, we can substitute it back into one of the original equations to solve for y. Let's use the first original equation:
3(-5) + 6y = 21
-15 + 6y = 21
6y = 36
y = 6
Therefore, the solution to the system of equations is:
x = -5, y = 6
( -5, 6)
Solving with Elimination Practice
Complete this assessment to review what you've learned. It will not count toward your grade.
5 of 55 of 5 Items
Question
Solve the system of equations.
3x+6y=21
–5x+2y=13 (1 point)
(
,
)
1 answer